O turismo industrial como potenciador do desenvolvimento local – estudo de caso do Museu do Vinho de Alcobaça em Portugal - António Valério Maduro; Alberto Guerreiro; Aurélio de Oliveira (PASOS Revista de Turismo y Patrimonio Cultural, 2015)
This work aims at the development of a management model and programme for the Wine Museum of Alcobaça in dialectic articulation with a political strategy of cultural stimulation and local development. By using a deductive methodology, we bring forward a theorethical reflection on the revitalization and redefinition of the industrial tourism linked to viticulture. Having in mind the context of the historical events of the museum, which encompass the social, cultural and territorial context, the institutional genesis and the changing of the authority, the analythical body grows from the notions of enotourism and industrial tourism as differenciating and stimulating elements of a sustainable development. In that sense, the museum takes its role as instigator of a process of social and economic transformation that involves a set of discourses and practices towards a change.